2017
DOI: 10.1080/10967494.2017.1297337
|View full text |Cite
|
Sign up to set email alerts
|

Municipalities’ Choices of Service Delivery Modes: The Influence of Service, Political, Governance, and Financial Characteristics

Abstract: This study investigates the influence of service, political, governance, and financial characteristics on municipalities' choices of four service delivery modes (in-house, inter-municipal cooperation, municipality-owned firm, and private firm)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 51 publications
5
45
0
1
Order By: Relevance
“…However, Hebdon and Jalette (2008) for Canada found that elected politicians reduce privatization rates and, therefore, have hesitation with a solid restructuring agenda. In addition, a recent study using Dutch local government data (Schoute, Budding, and Gradus 2017) showed that in this context, ideology plays a significant role in choices of service delivery modes, so the debate is still open.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hebdon and Jalette (2008) for Canada found that elected politicians reduce privatization rates and, therefore, have hesitation with a solid restructuring agenda. In addition, a recent study using Dutch local government data (Schoute, Budding, and Gradus 2017) showed that in this context, ideology plays a significant role in choices of service delivery modes, so the debate is still open.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical starting point of this study is the literature on contracting for public services, which frames the importance of political motives, institutional context, contractual arrangements, and service markets for contracting decisions and outcomes (Amirkhanyan, Kim, and Lambright 2010;Brown, Potoski, and van Slyke 2016;Entwistle and Martin 2005;Hart, Shleifer, and Vishny 1997;Hefetz and Warner 2012). Several public service contracting models have been discussed in the literature, including models based on competitive tendering, negotiations, and coorporation (Dehoog 1990;Schoute, Budding, and Gradus 2017). As mentioned in the introduction above, our focus here is limited to the former, which involves the award of public contracts through formal rounds of tendering among the providers in the private market.…”
Section: Theory Literature and Hypothesesmentioning
confidence: 99%
“…The finding suggests that, at least in the context of road and park services in Danish municipalities, tendering and contracting out is working relatively effectively as a political and/or organisational strategy for reducing the service delivery costs. An important point of notice is that contracting is used for many different (and sometimes competing) political, organisational, and economic reasons (Brown and Potoski 2003;Schoute, Budding, and Gradus 2017). Public organisations may thus focus on cost reductions to a varying extent, which is reflected in the economic results that municipalities obtain from contracting the service.…”
Section: Version Accepted For Publication In Local Government Studiesmentioning
confidence: 99%
See 2 more Smart Citations